A Project for the Synopia of the Integrated City. MODEL I: Harbor-Center with Water-Sea-Earth Communication Routes - Cattabriga, Ilaria (Histories of Postwar Architecture, 2021)
This paper wants to introduce Leonardo Ricci’s project for the integrated town identifiable on two kinds of archival series: the pictures of a three-dimensional model titled MODEL I: Harbor-center with water-sea-earth communication routes kept in Casa Studio Ricci in Florence and the bidimensional drawings kept in CSAC (Centro Studi e Archivio della Comunicazione) Archive, by framing it in his architectural work and research of the Sixties, which saw an intense exchange with the United States. It will be outlined in its fundamental aspects by explaining firstly the theoretical then the applied research Ricci dedicated to the elaboration of the model, as he maybe would have presented it according to its strong belief in the intertwining between these two layers. The final part will deal with a comparison of the analyzed project to the coeval model for the “Casa Abitata” exhibition, presented one year before in Florence. Both models show the same purposes and final similar morphological results, the first elaborated in the United States, the second one in Italy, as a consequence of Ricci’s research for a synthesis between architecture and sculpture and as a necessary melting between the physical and the social structures, thus the search for the most livable and useful spaces for the best development of modern life.